Cancer Stem Cell and Stromal Microenvironment - Li, Li (the Academic Division of Ochsner Clinic Foundation, 2013)
BACKGROUND: Chemotherapeutic resistance and local recurrence or distant organ metastasis are the major causes of cancer mortality. Conventional cancer treatments do not consistently prevent cancer recurrence. METHODS: We illustrate the key roles that cancer stem cells and the tumor microenvironment—particularly the lymph node stromal microenvironment—play in tumor drug resistance, metastasis, and recurrence in 2 representative cancers: colorectal cancer and follicular lymphoma. CONCLUSION: We believe that combination treatment with chemotherapeutic agents in conjunction with targeted therapies, such as stromal/cancer stem cell signaling–targeted therapy, may effectively minimize cancer recurrence.